EVALUATION OF H REFLEX AND F RESPONSE IN QUANTITATIVE MEASUREMENT OF SPASTICITY AND THEIR RELATION WITH CLINICAL MEASUREMENT METHODS IN PATIENTS WITH SPINAL CORD INJURY - Serap Tomruk,; Gülümser Aydın,; Işık Keleş,; Ö. Sibel Demir, (Archives of Rheumatology, 2002)
In this study, the parameters of H reflex and F response were evaluated in 21 patients with spinal cord injury and in a group of 20 healthy volunteers and compared between the groups. Also in patient group the relations of the electrophysiological parameters with the results of patientsÕ self reports of spasticity and the clinical spasticity measurement methods based on physical examination were investigated. In statistical analysis, amplitude ratio of Hmax/Mmax was increased, and the amplitudes of Fmax, Fmean, Mmax were decreased significantly in the patient group. When clinical and electrophysiological parameters obtained from the same side were analyzed statistically, mean deep tendon reflex score was found to be correlated positively with mean amplitude of Hmax. The increase in amplitude ratio of Hmax/Mmax in the patient group indicates that the excitability of alfa motorneurons is increased in patients with spinal cord injury. Besides, variations in F response and H reflex parameters were not parallel to each other, suggesting that H reflex is influenced not only from the excitability of alfa motorneurons but also the other pathophysiological mechanisms of spasticity. Clinical and electrophysiological methods showed weak correlation, which might be due to the reason that spasticity is a combination of neural pathophysiological mechanisms and while its clinical findings reflect this combination, each electrophysiological method assesses only one aspect of spasticity. Finally, these results suggest that more specific clinical tests should be developed for more accurate evaluation of spasticity.